AB0279 Rheumatoid factor and response to TNF antagonists in rheumatoid arthritis: Systematic review and meta-analysis of observational studies. (23rd January 2014) - Salgado, E.; Maneiro, J.R.; Carmona, L.; Gomez-Reino, J.J.
Abstract : Objectives: To explore whether baseline titer or positivity of rheumatoid factor (RF) are predictors of the response of rheumatoid arhtitis (RA) patients to tumor necrosis (TNF) antagonists. Methods: A systematic review and meta-analysis of observational studies were conducted. Pubmed, EMBASE, Cochrane and abstracts form ACR and EULAR were searched (up to June 2011). The search was limited to longitudinal studies. All studies on association between baseline RF (titer and/or status) and response to any TNF antagonists, or with enough data to estimate this association were included. Qualitative analysis and meta-analysis using random-effects approach by type of outcome response and RF test was performed. Risk of publication bias was also evaluated. Heterogeneity was tested using I 2, with I 2 value >40% defined as high levels Results: The systematic review included 18 studies of 4163 identified articles, involving 5703 patients with homogeneous baseline characteristics. The most common outcome measure to assess response was EULAR criteria, usually merging good and moderate categories as responder group. The weighted mean difference (WMD) of baseline IgM RF titer in meta-analysis was higher in the non-responders group [- 101.58 (95% CI -156.58, -46.59) I 2 =0.0]. Combined odds ratios (ORs) of positive IgM RF, positive IgA RF, and positive IgG RF to achieve good/moderate response were 1.08 (0.80, 1.47), I 2 =40.9%; 0.83 (0.39, 1.73), I 2 =39.8%, and 1.30 (0.48, 3.51), I 2 =62.9%, respectively. We did not find and association between positive IgM RF and EULAR good response or remission. Conclusions: This meta-analysis does not consistently support baseline IgM RF titer as a predictor of response to TNF antagonists in RA. Disclosure of Interest: E. Salgado: None Declared, J. R. Maneiro: None Declared, L. Carmona Speakers Bureau: LC has received lecture fees from Abbott and Pfizer, J. J. Gomez-Reino Grant/Research support from: JJ G-R has received research grants from Roche and Schering-Plough, Consultant for: JJ.G_R is on the Advisory Boards of BMS, Pfizer, Roche, Schering-Plough and UCB SA., Speakers Bureau: JJ G-R has received lecture fees from BMS, Roche, Schering-Plough and Wyeth